Kompetencja: słowo kluczowe czy „wytrych" w edukacji? - Czerepaniak-Walczak, Maria (Wydawnictwo Naukowe UAM w Poznaniu, 1999)
The aim of this article is to encourage and to contribute to, serious and constructive thinking about competency-based education. The particular focus of this text is on defining and operationalizing the key notion: competence, since it is clear that the unambiguous understanding will crucially affect the work of a teacher as a reformer. It is a useful concept in the context of discussing changes of education. Competence is defined as: an awared, dynamic, satisfactory, but not an unusual, skill necessary for coping with specific problems. It is an integral structure of knowledge, skills, understanding and desire which is demonstrated on the established standards. The present paper is concerned with reasons for defining the concept of competence, both theoretical and practical, its operationalisation and the criteria of its classification.
Competence: the key-word or “pass-key” in education?
Keywords: Kompetencje; Competences; Struktura kompetencji; Competency structure; Klasyfikacja strukturalna; Structural classification